Clinical assessment methods for scapular position and function. An inter-rater reliability study. (1st December 2020) - Larsen, Camilla Marie; Søgaard, Karen; Eshoj, Henrik; Ingwersen, Kim; Juul-Kristensen, Birgit
ABSTRACT: Introduction : The aim of this study was to assess the inter-rater reliability of selected static, semi-dynamic, and dynamic test assessment methods for evaluation of scapular positioning and function. Methods : A standardized three-phase (i.e. training, overall agreement, and actual study) protocol for reliability studies was applied on 41 overhead sports participants, aged 18–56 (22 with obvious scapular winging, classified as visibility of the medial or inferior angle border of scapula). Ten scapular test assessment methods (two static, three semi-dynamic, and five dynamic) were evaluated. Results : Bland–Altman plots showed no funnel effects, although systematic bias and significant differences between raters were present in three of the methods. ICC values ranged from 0.71 to 0.80 for the static test assessment methods and from 0.25–0.92 for the semi-dynamic test assessment methods. Three of the five dynamic test assessment methods had ICCs of 0.47–0.68. For the two remaining dynamic test assessment methods, kappa varied between −0.034 and 0.71. Using PABAK, kappa increased to 0.54–0.86. Conclusion : Four scapular test assessment methods (Upper horizontal distance, Lower horizontal distance at max shoulder flexion, Acromial distance, and Winging scapula) showed satisfactory inter-rater reliability. Simple visual observational methods and quantitative distance measurements have better reliability between clinicians than more complex measurements and may be better suited for use in clinical practice.